PROFITABILITY ANALYSIS OF CATFISH PRODUCTION IN ADO-EKITI, EKITI STATE, NIGERIA - Akoh, J.P.; Acheneje, P.; Oloniyo, R.B. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
Fish is a valuable source of protein rich in essential amino acids and crucial for human health and economic growth. The study assessed the profitability of catfish production in Ado-Ekiti. A multi-stage sampling procedure was adopted to randomly select 90 registered fish farmers, using structured questionnaires to collect primary data. Descriptive statistics and farm budgetary analysis were used to achieve the study’s objectives. The findings revealed a mean age of 49 years, 58% female, 71% married, and 73% educated, with an average household of 5 persons. The average total revenue per production cycle was ₦1,185,662.22, while the total cost was ₦ 1,037,295.10, consisting of ₦717,872.88 as total variable costs and ₦ 319,422.22 as total fixed cost. The net farm income was ₦148,367.12, with a gross margin of ₦ 467,789.34 and RoI of 14%. The profitability ratio was 0.13, suggesting for every N1 invested into catfish production, 13% (N 0.13k) was generated as profit. However, poor road networks with a mean of 2.44, and inadequate capital with a mean of 2.40 were the major challenges associated with catfish production. The study concludes that catfish production is relatively profitable in Ado Ekiti. Therefore, it is recommended that the State Government ensure adequate provision and maintenance of a good road network, and develop a robust cold chain infrastructure based on public-private partnership (PPP) to reduce post-harvest losses and maintain product quality in the study area.